Nutritional status and associated factors among high school students at central region of Vietnam: a cross-sectional study - Tran, Thi Tao; Tran, Binh Thang; Hoang Vu, Nhat Kha; Phan, Thi Cam Van; Le, Kim Oanh; Le, Thi Thuy; Kieu, Anh Phon; Tu, Ngoc Minh Tram; Phan, Thanh Tung (Tạp chí Y Dược Huế, 2026)
Background: Adolescents are a vulnerable group to malnutrition. However, there is a lack of research on the nutritional status of high school students, a group in a critical in the transitional phase from adolescence to adulthood. Our study aims to investigate the nutritional status and associated factors among high school students at central region of Vietnam. Method: We conducted a cross-sectional study with 739 students from four high schools in Hue City. Nutritional status was assessed using height-for-age and BMI-for-age indicators based on the WHO 2007 standards. Demographic characteristics and dietary behaviors were collected through a self-administered questionnaire. Logistic regression models were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) to explore factors associated with nutritional status of students. Results: Of the participants, approximately 3.2% were classified as stunted. About 6.0% were identified as thinness, while 11.9% and 2.6% were classified as overweight and obese, respectively. Additionally, students from high-income households were significantly less likely to be stunted (OR = 0.254; 95% CI: 0.076 - 0.853). Conclusion: Our study contributes to the growing evidence of the double burden of malnutrition among adolescents. Additionally, we highlight the significant influence of household income on stunting, underscoring the importance of improving economic conditions to achieve better nutritional outcomes.